Évolutions des théories linguistiques et détermination des choix normatifs de la langue corse - Di Meglio, Alain; Comiti, Jean-Marie; Cortier, Claude (My University, 2006)
Despite its historical lack of legal status, the Corsican language has never left linguists indifferent; since the end of the 19th and into the 20th Century, it has been the subject of two linguists atlases and an electronic database. Numerous studies, from the oldest to the most recent, have resulted in a variety of linguistic classifications in which Corsican has sometimes been used as an ideological tool: some have wished to pull Corsican into the Italian fold and others to draw it into the French linguistic sphere. It was not until the seventies that new and more objective descriptions of Corsican emerged, many written by Corsican researchers. The critical and theoretical framework that emerged from these studies proved useful for the way that Corsican language pedagogy has been conceptualized.
Keywords: Corsican language; classification; ideology; new description; taught language